Exploring the Use of Interactive Digital Media Applications to Enhance Literacy and Numeracy Skills in Elementary Education - Alda Permatasari; Annasriyah Masfufah; Margaretha Herlin Pratiwi; Novi Lestari; Selly Noverina; Yulita Devi Utami; Dian Nuzulia Armariena; Mega Prasrihamni (Sustainable, 2026)
This study aims to explore the use of interactive digital media applications to enhance literacy and numeracy skills in elementary education. Employing a qualitative descriptive approach, the research was conducted at SD Negeri 48 in Palembang City, Indonesia, involving teachers and students actively engaged in digital-based learning. Data were collected through classroom observations, semi-structured interviews, and documentation, and analyzed using an interactive model consisting of data reduction, data display, and conclusion drawing. The findings reveal that the integration of interactive digital media improves students’ literacy skills, including reading comprehension, vocabulary acquisition, and writing ability, as well as numeracy skills such as problem-solving, calculation, and data interpretation. In addition, the use of digital applications increases student engagement, motivation, and participation during the learning process. However, the implementation faced key challenges, primarily limited technological infrastructure and varying levels of teachers’ digital competence, alongside disparities in students’ digital literacy. Supporting factors such as teacher innovation, school support, and parental involvement were found to play a crucial role in mitigating these obstacles. The study concludes that interactive digital media holds strong potential to enhance learning outcomes in elementary education when supported by adequate infrastructure, targeted capacity building, and collaborative efforts among stakeholders.